2017
DOI: 10.20870/oeno-one.2017.51.1.1814
|View full text |Cite
|
Sign up to set email alerts
|

Improving phenolic and chromatic characteristics of Monastrell, Merlot and Syrah wines by using two elicitors

Abstract: Aims: Phenolic compounds, including anthocyanins, flavonols and tannins, are considered very important from a health and technological point of view. While the concentration of these compounds in grapes depends on many factors, elicitors may be regarded as a new strategy for increasing their content in grapes and, consequently, in wines. Methods and results:Berries of three grape varieties (Monastrell, Merlot and Syrah) were sprayed with two elicitors, BTH (benzothiadiazole) and MeJ (methyl jasmonate), during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The treatment with CaCO 3 caused increases of flavan-3-ols in grapes and wines, including catechin, epicatechin, and the procyanidins B1 and B2. Similar increases of flavan-3-ols have been observed for 'Yan 73', 'Cabernet Sauvignon', 'Merlot', and 'Monastrell' grapes and wines from ABA-or MeJA-treated vines [32,42]. The flavan-3-ols accumulate in grape seeds [2], and their release during the wine making process contributes to the organoleptic quality of the final product, especially on wine bitterness (monomeric forms of flavan-3-ols such as catechin and epicatechin) and astringency [45].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The treatment with CaCO 3 caused increases of flavan-3-ols in grapes and wines, including catechin, epicatechin, and the procyanidins B1 and B2. Similar increases of flavan-3-ols have been observed for 'Yan 73', 'Cabernet Sauvignon', 'Merlot', and 'Monastrell' grapes and wines from ABA-or MeJA-treated vines [32,42]. The flavan-3-ols accumulate in grape seeds [2], and their release during the wine making process contributes to the organoleptic quality of the final product, especially on wine bitterness (monomeric forms of flavan-3-ols such as catechin and epicatechin) and astringency [45].…”
Section: Discussionsupporting
confidence: 70%
“…The treatment of vines with CaCO 3 favored the accumulation of some flavonols in wine, but they were not observed in grapes. Gil-Muñoz et al [ 42 ] did not observe increases of flavonols in grapes (‘Syrah’ and ‘Monastrell’) treated in preharvest with MeJA, however, the wines made with these grapes had higher contents of flavonols as compared to control wines. These results suggest that the alcohol in wine is needed to the release of flavonols from grape tissues during the wine making process [ 43 ].…”
Section: Discussionmentioning
confidence: 96%
“…The presence of the trihydroxylated flavan-3-ol subunit, epigallocatechin, may reduce the coarse perception of astringency 29 and studies on quality grading of young red wines have indicated that the greater proportions of skinderived tannin subunits in the wine, the higher the perception of quality. 30 With regards to wines, our results show the wines of the new varieties obtained much higher concentrations of EGC compared to the Monastrell wines, suggesting that despite having large amounts of total PAs, we would be talking about new varieties with great oenological characteristics from an organoleptic point of view. Monastrell and MC4 wines had similar concentrations and lower than the rest of the varieties as occurred for the content total PAs (Fig.…”
Section: Tannin Composition In Grapes and Winesmentioning
confidence: 75%
“…Specifically, tannins are responsible for stabilising the colour and sensory characteristics of wines, such as astringency and bitterness (Chira et al, 2009). Seeds usually contain a higher concentration of tannins and a greater proportion of galloylated units (% Gal) than skins, whereas skin tannins have a higher mean degree of polymerisation (mDP) (Gil, 2017).…”
Section: Tannins In Grapes and Winesmentioning
confidence: 99%